2(n-2)=4n+6

Simple and best practice solution for 2(n-2)=4n+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(n-2)=4n+6 equation:


Simplifying
2(n + -2) = 4n + 6

Reorder the terms:
2(-2 + n) = 4n + 6
(-2 * 2 + n * 2) = 4n + 6
(-4 + 2n) = 4n + 6

Reorder the terms:
-4 + 2n = 6 + 4n

Solving
-4 + 2n = 6 + 4n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-4n' to each side of the equation.
-4 + 2n + -4n = 6 + 4n + -4n

Combine like terms: 2n + -4n = -2n
-4 + -2n = 6 + 4n + -4n

Combine like terms: 4n + -4n = 0
-4 + -2n = 6 + 0
-4 + -2n = 6

Add '4' to each side of the equation.
-4 + 4 + -2n = 6 + 4

Combine like terms: -4 + 4 = 0
0 + -2n = 6 + 4
-2n = 6 + 4

Combine like terms: 6 + 4 = 10
-2n = 10

Divide each side by '-2'.
n = -5

Simplifying
n = -5

See similar equations:

| 2x+3-20=500 | | 1.5x(6-4)= | | 3a=7c | | 2x+4=2x+3(-x+2) | | 500=100+3n | | 24n+72=288 | | log[2](3x+2)=log[3](12x+3) | | x(x)+7x-5=0 | | f(x)=2x^2+7x-1 | | s^2-13st-30t^2=0 | | 1.5x(6-4)=3 | | -7c-8(9-6c)= | | x(x)+16x+39=0 | | 5+2y=7 | | 6y-13=55 | | 8(y+9)=7y-3 | | solven+(n+1)+(n+2)=54 | | 25-n/2=10 | | 3(-1)-2(1/2) | | .2(-10x+25)=3x(-3-4) | | x^3+17x^2+41x+3=0 | | 25x-28=3x-10 | | x(x)+17x+60=0 | | x+4+8=4 | | 2sinx=3cosx+2 | | 5y-6/2=y-2-y/3 | | x+4+4=4 | | x=9.5c+32 | | y+76.7=170-77.15 | | (3m+5)=2m-4 | | 4(w+3)-2= | | 2(x-6)=4x+6 |

Equations solver categories